2018
DOI: 10.1186/s13104-018-3303-z
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarettes use and perception amongst medical students: a cross sectional survey from Sindh, Pakistan

Abstract: ObjectiveThe manufacturers of electronic cigarettes (e-cigarettes) are actively marketing their product through electronic and social media. Undergraduate medical students are expected to have better knowledge and awareness as they directly interact with patients in their training, The purpose of this study is therefore, to determine knowledge, use and perception regarding e-cigarettes among medical students from Sindh, Pakistan.ResultsA cross-sectional study was conducted between 1st July and 30th September 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
3
14
1
1
Order By: Relevance
“…In another study among health science students in Saudi Arabia, the lifetime prevalence of e-cigarettes vaping has been reported to be 27.7% [ 137 ]. In a study conducted in Pakistan on medical students, the prevalence of e-cigarettes vaping was 13.9% [ 139 ], while in another study, the current prevalence of e-cigarettes vaping was 4.4% on medical students and 12.4% on non-medical students [ 2 ]. It has been reported that the reason for the low prevalence among medical students maybe their high awareness of the dangers of e-cigarettes vaping during the period of their education course [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study among health science students in Saudi Arabia, the lifetime prevalence of e-cigarettes vaping has been reported to be 27.7% [ 137 ]. In a study conducted in Pakistan on medical students, the prevalence of e-cigarettes vaping was 13.9% [ 139 ], while in another study, the current prevalence of e-cigarettes vaping was 4.4% on medical students and 12.4% on non-medical students [ 2 ]. It has been reported that the reason for the low prevalence among medical students maybe their high awareness of the dangers of e-cigarettes vaping during the period of their education course [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The electronic cigarettes' popularity nowadays is rising globally, although data available on its safety and efficacy are limited. 24 And the rate of its awareness and usage are not known in some countries. 25 But some studies showed a significant rise in its awareness over recent years.…”
Section: Discussionmentioning
confidence: 99%
“…In Malaysia, a cross-sectional study using the 2011 version of the Global Adult Tobacco Survey (GATS) tool in six universities found that 74.9% of respondents reported smoking e-cigarettes, and 40.3% reported using both traditional and e-cigarettes (3). In the Middle East, studies among university students in Saudi Arabia reported prevalence levels between 10 and 27.2% (5)(6)(7)(8)(9), and a study conducted at five different medical colleges in Pakistan reported that 6.2% of the participants reported using e-cigarettes (10).…”
Section: Introductionmentioning
confidence: 99%